ANALISIS TAGANING DALAM TRADISI MUSIK GONDANG SABANGUNAN BATAK TOBA - LIMBONG ROSLINA (Saraswati)
The analysis of the instrument taganing in the traditions of music gondang sabangunan Batak Toba is an traditional instrument from the tribe of Batak Toba research, played in an instrumental music ensemble, that is existing in the midst life of the Batak Toba people namely is gondang sabangunan. This research used a descriptive qualitative research method with structural approach, functional approach and musicologist approach. Taganing is a traditional musical instrument derived from the Batak Toba, a five-pitched drum, one-sided and played by hammered or beaten. Taganing is one of the instruments in the ensemble gondang sabangunan, played together with other instruments like sarune bolon, gordang bolon, ogung and hesek. In the showing gondang sabangunan ensemble, taganing have highly diverse functions and the very important role the implementation of a musical performance gondang in the middle of the Batak Toba. These functions we can see and understand well with the conceptually, a musicologist, and specifically. Through all three of the above than functions taganing in the performance gondang sabangunan is as a means of communication, as a leader, decisive tempo, play the melody, play rhythmic variables, show virtuositas to add to the aesthetic against appearance gondang itself and the people who heard and continue to play at the beginning of the gondang performance to wait for the introduction of sarune bolon completed, so that impression of performances musical gondang not stopped. Keywords: taganing, gondang sabangunan, function.